3.6‐8.1 GHz CMOS balun with 1.8° in‐band phase difference by using capacitive balance compensation technique. Issue 4 (2nd January 2020) - Yang, Geliang; Tang, Kai; Wang, Zhigong
Abstract: In this letter, a passive ultra‐wideband balun with high balance performance is proposed. The balun is realized by using a pair of planar spiral coupled transmission lines and a capacitor which is responsible for the capacitive balance compensation. The straight‐forward scattering matrix derivation shows that the proposed structure can achieve full output balances both in amplitude and phase. For demonstration, two baluns with and without the compensating capacitor were designed and fabricated in a 65‐nm complementary metal‐oxide‐semiconductor (CMOS) process. The measured results show that the compensated balun features a measured insertion loss ≤5.2 dB and a return loss ≥10 dB from 3.6 to 8.1 GHz. Within such a wide frequency range, the measured amplitude and phase difference are ≤0.2 dB and 1.8°, respectively, which are much better than its uncompensated counterpart.